Le moment Atlantique de la dynastie des Winthrop au XVIIe siècle - Lauric Henneton (Les Cahiers de Framespa)
Using the case of the Winthrop dynasty, this essay explores the successive stages of an Anglo-American family’s expansion in an Atlantic world that was still nascent in the mid-17th century. This process is here referred to as atlanticization. The Winthrop brothers (the sons of Governor John Winthrop) and their uncle Emmanuel Downing managed to establish a network stretching from New England to the West Indies to the British Isles, the Wine Islands and as far as the African west coast (« Guinea »). However, in spite of this genuinely Atlantic configuration (polygonal and shifting) and not just transatlantic (bipolar), the political upheavals of the Restoration of the Stuart monarchy and a series of deaths in the family were to launch a contrary process of de-atlantization, just as Atlantic trade began to expand significantly. Beyond the sole commercial dimension, this paper considers the multiple and overlapping Atlantic worlds (family, diplomatic, imperial, missionary and scientific) in which the Winthrops were involved.